2021
DOI: 10.22541/au.161109198.88684400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prior use of therapeutic anticoagulation does not protect against COVID-19 related clinical outcomes in hospitalized patients: a propensity score-matched cohort study

Abstract: The hypercoagulable state observed in COVID-19 could be responsible for morbidity and mortality. In this retrospective study we investigated whether therapeutic anticoagulation prior to infection has a beneficial effect in hospitalized COVID-19 patients. 1154 COVID-19 patients admitted to 6 hospitals in the Netherlands between March and May 2020 were included. We applied 1:3 propensity score matching to evaluate the association between prior therapeutic anticoagulation use and clinical outcome, with in hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 27 publications
4
19
1
Order By: Relevance
“…Inconsistent results on the association between use of chronic therapeutic anticoagulation and outcome in COVID-19 have been published, probably because of the dissimilar cohorts and improper correction of imbalances in baseline characteristics, including comorbidities. [33][34][35] In propensity score-matched comparisons, 36,37 there were no statistically significant differences in mortality, time to mechanical ventilation, or length of hospital stay in patients who received and those who did not receive chronic anticoagulatory therapy (some of these data have been published in a preprint and have not been peer reviewed). 37 Additionally, several small case series describe major bleeding complications in patients with COVID-19 who received intermediate dosed thromboprophylaxis.…”
Section: Viewpoint Anticoagulation and Clinical Course Of Covid-19: Observational Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Inconsistent results on the association between use of chronic therapeutic anticoagulation and outcome in COVID-19 have been published, probably because of the dissimilar cohorts and improper correction of imbalances in baseline characteristics, including comorbidities. [33][34][35] In propensity score-matched comparisons, 36,37 there were no statistically significant differences in mortality, time to mechanical ventilation, or length of hospital stay in patients who received and those who did not receive chronic anticoagulatory therapy (some of these data have been published in a preprint and have not been peer reviewed). 37 Additionally, several small case series describe major bleeding complications in patients with COVID-19 who received intermediate dosed thromboprophylaxis.…”
Section: Viewpoint Anticoagulation and Clinical Course Of Covid-19: Observational Evidencementioning
confidence: 99%
“…[33][34][35] In propensity score-matched comparisons, 36,37 there were no statistically significant differences in mortality, time to mechanical ventilation, or length of hospital stay in patients who received and those who did not receive chronic anticoagulatory therapy (some of these data have been published in a preprint and have not been peer reviewed). 37 Additionally, several small case series describe major bleeding complications in patients with COVID-19 who received intermediate dosed thromboprophylaxis. [38][39][40] These findings under pinned the need for well designed and large randomised controlled trials on the efficacy and safety of anticoagulant treatment in patients with COVID-19.…”
Section: Viewpoint Anticoagulation and Clinical Course Of Covid-19: Observational Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies investigating the role of OACs prior to admission in patients with COVID‐19 have varied 13–19 Table IV. provides a summary of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it soon became clear that patients continued to have thrombotic events on prophylactic heparin ( Trimaille et al, 2020 ) and some studies suggested that using intermediate dose heparin was more effective ( Stessel et al, 2020 ; Meizlish et al, 2021a ) although other studies showed no benefit from the increased dose of heparin ( Investigators, 2021 ). One study found that therapeutic anti-coagulation in COVID-19 patients reduced the risk of pulmonary embolism but had no effect on mortality ( Spiegelenberg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%